Challenges Facing South African Financial Institutions When Establishing Work Teams in Africa - Ebrahim, Mubeen (My University, 2013)
Africa has been identified as an emerging market with an average GDP of more than 5% and countries from around the world have therefore realised the potential for business in Africa. Business initiatives require people to work in teams in order to make business possible. The study explores the challenges South African financial institutions face when establishing work teams in Africa. In-depth interviews were conducted using an open ended question to determine the experiences of leaders, directors, line managers and project managers with experience in team creation for South African financial firms, when doing business in Africa. The main findings were a set of challenges that have been categorised as, ‘Inherent Challenges’; ‘Approach Challenges’ for engaging with teams and other stakeholders; and ‘Implementation Challenges’ that Africa as a setting presented. The key message is the three categories may be applied to any business investigating the challenges of establishing teams and the study will be replicated.
MBA thesis
Keywords: Work teams; Teams; Ex-patriates; Banking institutions